Pengaruh Work Family Conflict dan Workload terhadap Burnout pada Ibu Pekerja : Studi Kasus di Perusahaan Multinasional - Apipah Apipah; Intaglia Harsanti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The dual roles carried out by working mothers in managing household responsibilities and fulfilling professional duties often create pressures that affect their physical, mental, and emotional well-being, thereby increasing the risk of burnout. This study aims to examine the influence of work family conflict and workload on burnout among working mothers. A quantitative approach was employed using purposive sampling, involving 136 respondents. Burnout was measured using dimensions of exhaustion, mental distance, cognitive impairment, and emotional impairment. Work family conflict was measured using dimensions of time based WIF, time based FIW, strain based WIF, strain based FIW, behavior based WIF, and behavior based FIW. Workload was measured using dimensions of work speed and work quantity. Data were analyzed through multiple linear regression. The findings indicate that work family conflict and workload, when considered simultaneously, have a significant effect on burnout. Partially, work-family conflict significantly influences burnout, whereas workload does not have a significant effect on burnout among working mothers in this study. The study also suggests that while workload is a relevant factor, its direct impact on burnout among working mothers may be mediated by other variables such as personal coping mechanisms, support systems, and organizational practices. The lack of a significant relationship between workload and burnout in this study may reflect the adaptation of working mothers to their work environments or the presence of supportive workplace policies that help mitigate the negative effects of workload. In conclusion, this study highlights the need for workplace interventions that address work-family conflict and provide adequate support to working mothers. It also emphasizes the importance of developing policies that help alleviate the pressures of dual responsibilities, thereby reducing the risk of burnout.